Effects of Licensing Reform on Firm Innovation : Evidence from India - Seker, Murat (2012)
The regulatory environment in a country can affect firm performance. This study investigates the impact of a particular regulation, namely license requirements for certain firm activities, on the innovation performance of Indian firms. First it presents a model of firm and industry evolution that explains the dynamics of multi-product firms. Then, using a firm level panel data set, it shows that removal of license requirements led to roughly 5 percentage points faster innovation rates where innovation is measured as introduction of new product varieties that had not existed in the market. The results are robust to inclusion of controls for the other policy reforms that occurred during the period of licensing reform.